(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Due to the prevalence of ankle malleolar fractures and by considering the influence of proximal tibiofibular joint(PTFJ) on fibula movement during ankle motion and subsequently on ankle injuries, this research was conducted to determine distributed frequency of the PTFJ in adult patients with malleolar fractures. Methods: This survey was conducted on a prospective cross-sectional basis. adult patients with malleolar fractures in two year period enrolled . Information, such as gender, age, mechanisms of fractures, reason of fractures, location of fractures was Collected, classified and reported along with descriptive statistics. Frequency of PTFJ in normal population determined and used for comparison with study group. Results: In the 79 patients could match our criteria in this study. The age of patients was 37±15 with range of 18-80 years. The highest number of ankle fractures were seen in third decade of age and these fractures were more prevalent in men. The most common cause of ankle fractures was traffic accidents (54/43%).the most common injury was lateral malleolar fracture (68/74%) and the most common mechanism of injury was Lauge-Hansen supination – external rotation, Danis-Weber type B . Frequency of PTFJ transverse and oblique types in normal population (80.6/19.4%)and study(71/29%) groups was statistically different (P < 0/05). According to mechanism of injury and location of fibular fracture, there was no significant difference between PTFJ types (P > 0/05). Conclusions: Frequency of oblique PTFJ in patients with malleolar fracture was more than normal population. There was no correlation between PTFJ type and mechanism of malleolar fracture or location of fibular fracture. Bangladesh Journal of Medical Science Vol.17(4) 2018 p.625-630